INTERPERSONAL FUNCTION OF AMERICAN POLITICAL SPEECH (SYSTEMIC FUNCTIONAL LINGUISTICS APPROACH) - Hieronimus Canggung Darong (IJOTL-TL (Indonesian Journal of Language Teaching and Linguistics))
This study is concerned with the interpersonal function analysis of American political speech text, by taking an example of first Obama's victory speech, based on Systemic Functional Linguistics theory (SFL). The speech text was modified into clauses which were subsequently analyzed in accordance with the goal of the analysis. The study revealed that the speech established an intimate relationship and a close distance with the audience which enables speaker to gain support and exchange information through the use of linguistics resources that are declarative clause in the mood structure, modality, and pronoun "we". This study has a great impact on language teaching and learning in terms of maintaining social relationships and exchanging meanings between teachers and students during their interactions in the classroom by taking into account the link between linguistic resources and the nature of text both spoken and written.